Thermostability enhancement of Escherichia coli phytase by error-prone polymerase chain reaction (epPCR) and site-directed mutagenesis - Xing, Hongguan; Wang, Pingping; Yan, Xing; Yang, Yi; Li, Xinliang; Liu, Rui; Zhou, Zhihua (Frontiers in Bioengineering and Biotechnology, 2023)
Phytase efficiently hydrolyzes phytate to phosphate; thus, it is widely used to increase phosphorus availability in animal feeds and reduce phosphorus pollution through excretion. Phytase is easily inactivated during feed pelleting at high temperature, and sufficient thermostability of phytase is essential for industrial applications. In this study, directed evolution was performed to enhance phytase thermostability. Variants were initially expressed in Escherichia coli BL21 for screening, then in Pichia pastoris for characterization. Over 19,000 clones were generated from an error-prone Polymerase Chain Reaction (epPCR) library; 5 mutants (G10, D7, E3, F8, and F9) were obtained with approximately 9.6%, 10.6%, 11.5%, 11.6%, and 12.2% higher residual activities than the parent after treatment at 99°C for 60 min. Three of these mutants, D7, E3, and F8, exhibited 79.8%, 73.2%, and 92.6% increases in catalytic efficiency (kcat/Km), respectively. In addition, the specific activities of D7, E3, and F8 were 2.33-, 1.98-, and 2.02-fold higher than parental phytase; they were also higher than the activities of all known thermostable phytases. Sequence analysis revealed that all mutants were substituted at residue 75 and was confirmed that the substitution of cysteine at position 75 was the main contribution to the improvement of thermostability of mutants by saturation mutagenesis, indicating that this amino acid is crucial for the stability and catalytic efficiency of phytase. Docking structure analysis revealed that substitution of the C75 residue allowed the mutants to form additional hydrogen bonds in the active pocket, thereby facilitating binding to the substrate. In addition, we confirmed that the intrinsic C77-C108 disulfide bond in E. coli phytase is detrimental to its stability.